Audiodescrição e cidadania : processos comunicacionais de sujeitos cegos vinculados aos usos e apropriações da rede social WhatsApp - Campanhã, Marcela Ribas (Universidade do Vale do Rio dos Sinos, 2020)
This research seeks to investigate the communicational processes in the uses and appropriations of digital media by people with visual impairment (PVI), in the perspective of their communicative citizenship. The investigation involves two aspects: the relation with the audio description and the use of WhatsApp social media. To understand the complexity of the object of this investigation, we present the contextualization of aspects related in the matter of visual impairment in a Brazilian context, the overview of the audio description and the communicational and digital inclusion of blind people in the mediatization processes, with digital focus. The research is based on theoretical arguments that works through the concepts of mediatization, digital communication and assistive technology, communicative citizenship, reception, uses and appropriations.We also present aspects involving blindness and audio description. To carry out the investigation about the uses of media and WhatsApp by blind communicating subjects, this research was carried out in a transmethodological approach (Maldonado 2008) involving exploratory research, bibliography and research of researches, participant observation and in-depth interview with reports of the life trajectories or four blind subjects. The results indicate that, in relation to the uses and appropriations that these subjects make in digital environments it is possible to say that they present similarities in relation to the uses and appropriations of people without visual impairment. The difference is that for PVI it is necessary to adapt to a communicational context that is hegemonic thought out for people without visual impairment. We also found that the development of assistive technologies facilitates the process of accessibility and inclusion of these people, however, for communicative citizenship to be a reality, other factors of a legal, social and cultural nature are necessary.
Keywords: Cidadania; Audiodescrição; Comunicação; WhatsApp; Apropriações; Citizenship; Áudio description; Communication; WhatsApp; Appropriations; ACCNPQ::Ciências Sociais Aplicadas::Comunicação